Relationship between type of school, principals’ management approaches and level of students’ discipline in public secondary schools in Nyandarua and Laikipia districts, Kenya. - Kiumi, J. K.; Bosire, Joseph N.; sang, A. K. (BACHUDO SCIENCE CO. LTD PRINTED IN NIGERIA, 2008)
Students’ discipline is critical to the attainment of positive school outcomes. Level of students’ discipline depends on whether the principal- as the chief executive of the school- enlists the support of teachers and parents in discipline management. The study hypothesized that an inclusive discipline management approach is more likely to increase teachers’ and parental input on discipline management. This may in turn raise the level of discipline. The study investigated and analyzed the relationship between principals’ management approaches and level of students’ discipline in selected public secondary schools in Nyandarua and Laikipia districts, Kenya. Analysis of the relationship was based on school- size. Data were collected using a self-administered questionnaire from a sample of 211 teachers, 28 principals and 22 chairpersons of parent- teachers’ association. Data were analyzed using frequency counts and percentages and hypotheses tested using chi- square at 0.05 level of significance. The key findings revealed that principals heading large-sized schools were more inclusive compared to their counterparts in small schools. In addition, level of teachers’ and parental input on discipline management increased with increase in school-size. However, the level of students’ discipline was negatively related with school-size. These findings have important implications on school management with respect to training of principals and enhancing students’ discipline.
online
Keywords: Principal; Management approach; Students’ discipline